Sintesis Graphene Oxide (GO) dari Grafit Limbah Baterai dengan Modifikasi Metode Hummer - Atika Putri Karina; Chandra Wahyu Purnomo; Teguh Ariyanto (UM Purwokerto Press, 2026)
Graphene oxide (GO) is a carbon-based material with great potential for gas adsorption applications due its large surface area and abundant oxygen-containing functional groups. This study aims to synthesize GO from spent lithium-ion battery graphite through an enviromentally friendly modification of the Hummer method. The modification involved varying the intercalation media using hydrogen peroxide (H2O2), sulfuric acid (H2SO4) and their combination to evaluate their effect on the oxidation of potassium permanganate (KMnO4), heating, and post-reduction with H2O2. The structural evolution of graphite and the obtained GO was analyzed using Raman spectroscopy, where the ID/IG ratio was used an indicator of defect density. Result revealed that was battery graphite exhibited a higher degree of structural disorder than commercial graphite, with an increase ID/IG ratio from 0.12 to 0.32. After oxidation the ID/IG ratio increased to 0.33 for GO synthesized with mixed media (H?SO? + H?O?) (GO-mix), 0.94 for GO synthesized with H?SO? (GO-HM), and 1.36 for GO synthesized with H?O? only (GO-PT H2O2). The highest ratio observed in GO-PT H?O? indicates the most effective oxidation and the formation of abundant oxygen functional groups without KMnO? degradation. Therefore, using H?O? as a single intercalation agent offers a simple, efficient, and sustainable approach for producing high-quality graphene oxide from waste battery graphite.